2021
DOI: 10.1002/anie.202112251
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Catalyzed Monofluoroalkylation: Strategies for the Synthesis of Alkyl Fluorides by C−C Bond Formation

Abstract: Alkyl fluorides modulate the conformation, lipophilicity, metabolic stability, and pKa of compounds containing aliphatic motifs and, therefore, have been valuable for medicinal chemistry. Despite significant research in organofluorine chemistry, the synthesis of alkyl fluorides, especially chiral alkyl fluorides, remains a challenge. Most commonly, alkyl fluorides are prepared by the formation of C−F bonds (fluorination), and numerous strategies for nucleophilic, electrophilic, and radical fluorination have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 166 publications
0
14
0
Order By: Relevance
“…Catalytic methodologies based on (i) fluorination of alkenes, enol(ates), phenols and C–H bonds with electrophilic fluorinating reagents 3 or in (ii) transformations of fluorine-containing starting materials, 4 can be considered the most developed approaches for the regio- and enantioselective construction of fluorinated tertiary stereocenters. However, they respectively employ electrophilic fluorinating reagents – which are derived from fluorine gas – and use pre-functionalized fluorinated starting materials that could need multistep synthetic sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic methodologies based on (i) fluorination of alkenes, enol(ates), phenols and C–H bonds with electrophilic fluorinating reagents 3 or in (ii) transformations of fluorine-containing starting materials, 4 can be considered the most developed approaches for the regio- and enantioselective construction of fluorinated tertiary stereocenters. However, they respectively employ electrophilic fluorinating reagents – which are derived from fluorine gas – and use pre-functionalized fluorinated starting materials that could need multistep synthetic sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Geminal dihalides are versatile building blocks for constructing valuable monohalo derivatives through transition-metal-catalyzed selective carbon–carbon cross-coupling reactions. However, the catalytic and asymmetric coupling has been studied less, possibly due to the lack of a suitable catalytic system . Fu et al reported the enantioselective formation of tertiary alkyl fluorides through nickel-catalyzed Negishi couplings of racemic α-halo-α-fluoroketones in good yields and excellent ee .…”
Section: Introductionmentioning
confidence: 99%
“…To address the issues and challenges in direct C−F bond formation, we sought inspiration from the retrosynthetic analysis of aliphatic fluorides where the strategical disconnection of C−C bond would result in an alternative path via transition metal catalyzed C−C(R f ) cross‐couplings [27–32] . Compared with direct C−F bond formation, C−C couplings via transition metal catalysis could offer a facile, efficient, and highly selective approach to “diversity‐oriented” syntheses (DOS) of aliphatic fluorides under mild conditions with excellent functional group tolerance [33, 34] . However, the conventional fluorine‐containing raw materials and precursors were either difficult to be handled with due to their often gaseous nature (H 2 CFX, etc.…”
Section: Introductionmentioning
confidence: 99%